Some historical notes on popliteal cysts - P. Marson; M. Rippa Bonati; D. Tietto; L. Punzi (PAGEPress Publications, 2001)
Popliteal cysts, more appropriately those involving the gastrocnemio-semimembranous bursa, are traditionally known as "Baker's cysts", since in 1877 the English surgeon William Morrant Baker published a paper on this topic ("On the formation of synovial cysts in the leg in connection with disease of the knee-joint"). As a matter of facts, some authors described popliteal cysts before Baker. In particular, in 1856 a French physician, E.Foucher, performed a clinical and experimental study on 18 patients, focusing on some important aspects on the semeiology and pathophysiology of popliteal cysts. In 1861, Pietro Antivari, a physician from Friuli, a northeastern region of Italy, graduated at the University of Padova by producing an interesting paper on the popliteal cysts ("Dell'idrope delle borse mucose poplitee con tre osservazioni"). In the present historical note we report in full one out of three cases described by Pietro Antivari.